1988
DOI: 10.1139/g88-114
|View full text |Cite
|
Sign up to set email alerts
|

Genetic components of chromosome behaviour in Papaver somniferum L.

Abstract: PATRA, N. K., and CHAUHAN, S. P. 1988. Genetic components of chromosome behaviour in Papaver somniferum L. Genome, 30: 677 -679. Three nuclear variables, namely chiasma frequency, internuclear variation of chiasmata, and numerical deviations in the chromosomes of pollen mother cells, referred to as meiotic lability, were studied in 5 x 5 diallel crosses of Papaver somniferum L. Chiasma frequency and meiotic lability were controlled by both additive and dominant gene actions and internuclear chiasmata variance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

1994
1994
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
1
0
2
Order By: Relevance
“…The overall study showed co-linearity between the treatments and chromosomal abnormalities. PATRA et al (1987), PATRA and CHAUHAN (1988) and CHAUHAN (1989) have studied cytological variations (both mitotic and meiotic) in opium poppy and emphasized that opium poppy is good material for the study of nuclear and chromosomal behaviour with respect to mitosis and meiosis. In the present study, the meiotic variation was taken up to unravel the effect of mutagens on chromosomes in addition with an apparent comparison of mutagenic effect on both the varieties with respect to alkaloidal variations and physiological damages.…”
Section: Discussionmentioning
confidence: 99%
“…The overall study showed co-linearity between the treatments and chromosomal abnormalities. PATRA et al (1987), PATRA and CHAUHAN (1988) and CHAUHAN (1989) have studied cytological variations (both mitotic and meiotic) in opium poppy and emphasized that opium poppy is good material for the study of nuclear and chromosomal behaviour with respect to mitosis and meiosis. In the present study, the meiotic variation was taken up to unravel the effect of mutagens on chromosomes in addition with an apparent comparison of mutagenic effect on both the varieties with respect to alkaloidal variations and physiological damages.…”
Section: Discussionmentioning
confidence: 99%
“…Показано, что процессы геномной изменчивости в онтогенезе регу лируются генами (см. [18,[224][225][226]). Из вышеизложенного следует, что функционирование этих генов зависит, вероятно, как от внешних, так и от внутренних факторов (сигналов).…”
unclassified
“…10, № б Показано, что процессы геномной изменчивости в онтогенезе регу лируются генами (см. [18,[224][225][226]). Из вышеизложенного следует, что функционирование этих генов зависит, вероятно, как от внешних, так и от внутренних факторов (сигналов).…”
unclassified